ICJ AS THE UNIVERSAL BODY FOR RESOLVING DISPUTES RELATED TO THE APPLICATION OF TREATIES - KARVATSKA, SVITLANA; TORONCHUK, IVAN (Ehrlich’s Journal, 2023)
The article analyzes the interpretive activity of the International Court of Justice (ICJ) as the central judicial body of the United Nations (UN). The maintenance of international peace is one of the main goals of the United Nations and the activities of the United Nations Security Council (UNSC). Among the international courts, the ICJ is the universal body for resolving disputes related to the application of treaties and the most authoritative one in interpreting such treaties. The growing number of appeals to the courts to clarify and resolve disputes, the growing role and activity of courts in interpreting international law, the desire to interpret the treaty independently (authentically) in the form of subsequent agreements, and the strengthening of the ICJ peacekeeping mission in the context of political expediency in complicated cases controversial issues of international relations demonstrate the actualization of the appeal to the problem of treaties interpretation by the ICJ. The article argues that the treaties interpretation has become the basis for the practice of judicial precedent by international judicial bodies, which often refer to their previous decisions and decisions of other international judicial bodies in treating a particular case. It is essential to understand the role and features of the UNCS in treaty interpretation to resolve international disputes in modern conditions, which is part of the problem of resolving international legal relations between states and international organizations to maintain international law and order by resolving international disputes. In conclusion, it is noted that the consideration of cases by the ICJ is carried out in strict compliance with the Jus Cogens standards, which are specified in the Vienna Convention on the Law of Treaties (VCLT), as the basis of the mechanism for their recognition, as well as the principles of good faith and granting terms their usual meaning. International case law shows the evolution of the interpretation rules by the ICJ and the dominance of the principle of dynamicity.